The prevalence of lobular carcinoma in situ and its variants of breast cancer in Maharaj Nakorn Chiang Mai Hospital over a 5-year period - Rattanasalee, Suchanan; Chaiwun, Benjaporn; Sukhamwang, Neelaya (Biomedical Sciences and Clinical Medicine, 2024)
Objectives a) To study the prevalence of Lobular carcinoma in situ (LCIS) breast cancer and its variants, b) to evaluate the E-cadherin immunohistochemical staining patterns of LCIS and ductal carcinoma in situ (DCIS) and c) to evaluate the type of LCIS and co-existing invasive components. Methods This was a retrospective review of H&E and E-cadherin stained slides in cases diagnosed LCIS between 2006 and 2010. The results were recorded and analyzed. Results From 1,385 cases of breast cancer, 176 contained in situ components of which 19 (10.8%) were LCIS, with 16 (84.2%) of them being classical LCIS (CLCIS) and 3 (15.8%) pleomorphic LCIS (PLCIS). E-cadherin expression between LCIS and DCIS were different. Seven cases (43.8%) of 16 CLCIS revealed no expression, while 5 (31.3%) revealed focal expression and 4 (25.0%) focal positive loss of expression. Of 163 DCIS cases, 126 (77.4%) demonstrated strong expression, whereas 21.5% and 1.2% revealed faint and focal loss of expression, respectively. All 19 (100%) LCIS cases were coexisting with invasive carcinoma. Conclusions There is still a need to distinguish between LCIS and DCIS. Awareness of a possible encounter of a non-classical type LCIS during daily practice is important, due to different management. E-cadherin immunohistochemical staining is useful for confirming the diagnosis of LCIS. Clinical follow-up to define the natural history and most appropriate management for CLCIS and its variants should be carried out.